MANZANERO, Delia (2016): El legado jurídico y social de Giner. Madrid: Publicaciones de la Universidad Pontificia Comillas. - Manuel López Forjas (Daimon)
Reseña del libro: MANZANERO, Delia (2016): El legado jurídico y social de Giner. Madrid: Publicaciones de la Universidad Pontificia Comillas.